2021
DOI: 10.20944/preprints202110.0326.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Numerical Investigation of Cu<sub>2</sub>O as Hole Transport Layer for High-Efficiency CIGS Solar Cell

Abstract: Copper indium gallium selenide (CIGS) is an inexpensive material that has the potential to dominate the next-generation photovoltaic (PV) industry. Here we detail computational investigation of CIGS solar cell with encouragement of adopting cuprous dioxide (Cu2O) as a Hole Transport Layer (HTL) for efficient fabricated CIGS solar cells. Although Cu2O as a HTL has been studied earlier for perovskite and other organic/inorganic solar cell yet no study has been detailed on potential application of Cu2O for CIGS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Additionally, the V oc was also increased (without Cu 2 O: V oc = 1.12 V, with Cu 2 O: V oc = 1.20 V), perhaps due to the decrease of recombination [52]. The wide gap band of Cu 2 O reduces recombination losses and pulls holes from the absorber, allowing for smoother extraction of the holes while experiencing lower resistance [53]. Meanwhile, Albert et al found that the deposition of CuOx does not degrade the surface of perovskite or introduce traps at the interface by adding a layer of CuOx between the PTAA and the anode [54].…”
Section: The Effect Of a Cu 2 O Buffer Layer With Htlsmentioning
confidence: 99%
“…Additionally, the V oc was also increased (without Cu 2 O: V oc = 1.12 V, with Cu 2 O: V oc = 1.20 V), perhaps due to the decrease of recombination [52]. The wide gap band of Cu 2 O reduces recombination losses and pulls holes from the absorber, allowing for smoother extraction of the holes while experiencing lower resistance [53]. Meanwhile, Albert et al found that the deposition of CuOx does not degrade the surface of perovskite or introduce traps at the interface by adding a layer of CuOx between the PTAA and the anode [54].…”
Section: The Effect Of a Cu 2 O Buffer Layer With Htlsmentioning
confidence: 99%
“…The aim of the present study is to boost the parameters of SC by declining the recombination rate at the buffer layer. For this, two different buffer layers are taken; in addition, a BSF layer is also taken to minimize the overall rate of recombination in the buffer and window layer 19–21 . The silver sulfide (Ag 2 S) quantum dots are one of the newest items designed to enhance the SC's adaptability towards ultraviolet radiation and increase its absorption.…”
Section: Introductionmentioning
confidence: 99%